Unequal benefits: the effects of health insurance integration on consumption inequality in rural China - Han, Linlin (Frontiers in Public Health, 2025)
IntroductionUnlocking the consumption potential of rural residents and narrowing the consumption gap is crucial for expanding domestic demand and enhancing social equity. This study examined how integrating Urban-Rural Residents Medical Insurance (URRMI) affected consumption inequality among rural residents and its underlying mechanisms.MethodsWe analyzed 17,092 observations from the China Family Panel Studies (CFPS) 2012-2018. Consumption inequality was measured using the Kakwani relative deprivation index. A staggered difference-in-differences (DID) design with high-dimensional fixed effects was employed to analyze the impact of the urban-rural health insurance integration policy on consumption inequality. Robustness checks such as placebo tests, heterogeneity in treatment effects, and spatial spillover analyses were addressed.ResultsThe findings reveal that the policy significantly raises consumption levels among middle and high-income groups while concurrently reducing expenditures for the lowest-income bracket, exacerbating consumption inequality. Heterogeneity analysis indicates that the impact of urban-rural health insurance integration on rural consumption inequality is manifested in both consumption structure and life-cycle effects, with the most significant disparities observed in subsistence and enjoyment consumption, particularly among middle-aged and older age groups. Mechanism analysis identifies increased utilization of medical services, the release of precautionary savings among middle and high-income cohorts, and variations in health insurance funding modalities as key drivers of the widening consumption inequality gap.DiscussionThe study concludes with recommendations to promote the establishment of parity in urban-rural integrated health insurance and to prioritize policy support for vulnerable groups, especially the older adult and impoverished households.